Migration, Remittances, and Male and Female Employment Patterns - Amuedo-Dorantes, Catalina; Pozo, Susan (American Economic Review, 2006)
Little is known about the microeconomic impacts of workers ’ remittances despite their magnitude in countries with considerable out-migration. Reports that families receiving international remittances severely curtail their work efforts are fairly common in the popular press (e.g. Frank 2001). Yet, we lack rigorous analyses of how male and female labor supplies respond to increases in remittance income to either support or refute these anecdotal observations. According to the neoclassical model of labor-leisure choice (Killingsworth 1983), remittances –a source of non-labor income – may lift budget constraints, raise reservation wages and, through an income effect, reduce the employment likelihood and hours worked by remittance-receiving individuals. However, the receipt of remittances is usually preceded by the out-migration of working-aged household members, which may induce changes in the labor supply of non-migrating household members in order to compensate for forgone income or to defray migration-related expenses. Distinguishing the disruptive effect from the income effect of remittance inflows is problematic as most surveys do not contain detailed information on household out-migration and remittance receipt. However, to the extent that these two effects are expected to have opposite impacts on labor supply, we can assess which effect dominates. The impact of remittances on the decision to work has been previously examined by Rodriguez and